Market Share Islamic Banking In Indonesia - Hasan, Zulfikar (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2019)
At the end of 2016, the Islamic banking market share stood at 356.5 trillion Indonesian rupiahs (26.7 billion), equivalent to 5.03 per cent of the total banking sector’s assets. Islamic banking assets have risen faster year-on-year compared to conventional banking, registering a growth of 8.8 per cent in 2015 and 20.3 per cent in 2016. The performance of the Islamic banking industry in Indonesia has yet to satisfy the public’s expectations. Although with a market of more than 200 million Muslims, Islamic banks in Indonesia still face difficulties luring more customers and increasing their assets. For three consecutive years, the market share of the sharia banks in the country stood still at less than 5 per cent. According to the Global Advisors Islamic Finance Outlook Report for 2016, no Indonesian Islamic banks were ranked in the top five largest banks based on assets in Southeast Asia. This is an alarming situation for the industry and regulators. Thus, it evokes a question: Is the market becoming saturated for Islamic finance? This study aims to determine the factors that affect the market share of Islamic banks in Indonesia. With a focus on four main items, Islamic banking regulations, Islamic banking inclusion and literacy are still low from conventional banks, Islamic banking still does not have sufficient capital and the number and quality of Human Resources (HR) that are inadequate. This study uses an analytical descriptive study is to describe and analyzed data obtained based on primary and secondary data. While the method used is normative and focused on the study of literature, which is then analyzed qualitatively juridical.